1966
DOI: 10.1029/jz071i022p05283
|View full text |Cite
|
Sign up to set email alerts
|

The focal mechanism of the Alaska earthquake of March 28, 1964, and of its aftershock sequence

Abstract: Focal mechanisms have been determined for one preshock, for the main shock, and for more than 25 aftershocks of the Alaska earthquake of March 28, 1964. For the main shock a single nodal plane with a strike azimuth of 66°, dip 85° southeast, is determinable from the polarity of the P wave. This plane may be taken either as a plane normal to the fault motion (thrust faulting) or as the fault plane (dip‐slip motion on a near‐vertical plane). A combination of P wave first motion and S wave polarization data make … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

1972
1972
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(67 citation statements)
references
References 8 publications
0
67
0
Order By: Relevance
“…In a landmark 1965 paper, U.S. Geological Survey (USGS) geologist George Plafker [Plafker, 1965] convincingly showed that the only fault configuration consistent with the pattern of deformation was a "megathrust" on the low-angle fault plane. Analysis of the aftershock sequence supported this interpretation [Stauder and Bollinger, 1966]. Plafker's work provided the geologic field evidence that helped to explain where oceanic crust, initially created at mid-ocean ridges, is eventually consumed.…”
Section: Plate Tectonics In Actionmentioning
confidence: 59%
“…In a landmark 1965 paper, U.S. Geological Survey (USGS) geologist George Plafker [Plafker, 1965] convincingly showed that the only fault configuration consistent with the pattern of deformation was a "megathrust" on the low-angle fault plane. Analysis of the aftershock sequence supported this interpretation [Stauder and Bollinger, 1966]. Plafker's work provided the geologic field evidence that helped to explain where oceanic crust, initially created at mid-ocean ridges, is eventually consumed.…”
Section: Plate Tectonics In Actionmentioning
confidence: 59%
“…The absence of a Benioff zone beneath the continental margin off Oregon and Washington seems to indicate that subduction is not taking place, yet some observations are enticingly suggestive of subduction, such as the folded Pliocene and Pleistocene sediments of the Oregon lower continental slope. Similarly, off Alaska, the deformation during the great 1964 earthquake and the results of focal-mechanism studies are most easily explained by underthrusting (Plafker, 1969;Stauder and Bollinger, 1966). Thus some field observations support the theory and others conflict with it.…”
Section: Introductionmentioning
confidence: 87%
“…ago, the section that was depressed to form it should contain a former continental-rise type of sedimentary wedge. However, no such feature appears in seismic records in the depressed section below the trench fill (von Huene, 1972), and any previous rise or trench must now be incorporated into the continental slope. Since the Aleutian Trench is one component of a tectonic system that includes the Kenai and Chugach mountains, the trench may have begun to form at the same time as these mountains, in the early or middle Miocene.…”
Section: Existing Aleutian Trench Site 180mentioning
confidence: 99%
See 2 more Smart Citations